THE EFFECT OF ACUPRESSURE THERAPY ON THE INTENSITY OF LOWER BACK PAIN IN THIRD SEMESTER OF PREGNANCY - Fatimah Tulwazniah; Juraida Roito Harahap; Lailiyana; Ari Susanti (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
Lower back pain is one of the discomforts experienced by pregnant women that can interfere with daily activities. One of non-pharmacological methods for dealing with lower back pain is acupressure therapy. The purpose of this study was to determine the effect of acupressure therapy on the intensity of lower back pain in third trimester of pregnancy. This research is a Pre-Experiment with a one group pretest posttest design approach. The population in this study was women in the third trimester who examined their pregnancies in Puskesmas Payung Sekaki in January-March 2020. The samples are 20 women in their third trimester of pregnancies with the complaints of lower back pain. Samples were taken by purposive sampling. The data collection method was an observation method using data collection tools such as Numeric Rating Scale (NRS). The test used is the Wilcoxon Test with a significance level of 95%. The results of the average intensity of lower back pain in the samples before being given the acupressure therapy was 4.45 (SD = 1,234), and after being given the acupressure therapy was decreased to 1.25 (SD = 1,020). There was an effect of acupressure therapy on the intensity of lower back pain in the women in the third trimester of pregnancies (p = 0,000).